The The Effect of Doses Quail Manure on The Growth and Yield of Shallot (Allium ascalonicum L.) - Friza Elinda; Renfiyeni Renfiyeni; Muharama Yora; Metri Angga Putra; Firsta Ninda Rosadi (JERAMI : Indonesian Journal of Crop Science, 2022)
Research on the effect of Quail Manure on the Growth and Yield of Shallots (Allium ascalonicum L.), has been carried out in Jorong Lima Ninik, X Koto Singkarak District, Solok Regency with an altitude of ± 400 m above sea level. This study aims to obtain the best dose of quail manure for the growth and yield of shallots. The method used was a Randomized Block Design (RAK) with 6 treatments, 4 groups. The treatment given was the dose of quail manure namely, as follows: P1=0 g/polybag, P2=30 g/polybag, P3=60 g/polybag, P4=90 g/polybag, P5=120 g/polybag, P6=150 g/polybag. The research data were analyzed for variance if the calculated F was greater than F table 5%, followed by Duncan's New Multiple Range Test (DNMRT) at a 5% significance level. Parameters observed were plant height (cm), number of leaves (strands), number of tubers (fruit), wet weight (g), dry weight (g). The results showed that the application of quail manure had a very significant effect on plant height, the number of leaves, wet weight, and dry weight of shallot bulbs. The best results were obtained from the P5 treatment (120 g/polybag) with a production of 78.25 g/plant.